Online Based Academic Information System (case Study: SD. Hidayatur Rohman Asemrowo Surabaya) - Rifki Fahrial Zainal; Rani Purbaningtyas; Mustofa (JEECS (Journal of Electrical Engineering and Computer Sciences), 2019)
The influence of technology is very large, especially in the development of information. Accurate, fast, and precise information is very important for life today because information becomes a necessity in conveying something. The use of computers is one of the developments in information that is very useful because it can perform data processing, making reports and sending information remotely and in determining the potential of students. Determination of the potential is absolutely necessary by the school agency, namely the school, the guidance teacher has an important role in granting status to students. Determination of student potential requires special professional handling, because it involves the success of students in facing the examinations that will be given. Mistakes in determining students' readiness to face national exams can negatively affect the process and results of student exams themselves. So we need a method that can help minimize the impact of mistakes when determining the potential of these students, namely by grouping data techniques from the results of data mining. The need for data mining becauseof the large amount of data that can be used to produce useful information and knowledge. Naïve Bayes is a machine learning method that uses probability calculations. The use of this algorithm is considered appropriate because Naive Bayesian Classifier is one classification algorithm that is simple but has high capability and accuracy.